Efficacy Of Dual-Task Training With Two Different Priorities Instructional Sets On Gait Parameters In Patients With Chronic Stroke - Sengar S; Raghav D; Verma M; Alghadir AH; Iqbal A (Neuropsychiatric Disease and Treatment, 2019)
Shilpi Sengar,1 Deepak Raghav,1 Meenakshi Verma,1 Ahmad H Alghadir,2 Amir Iqbal2 1Department of Physiotherapy, Santosh Medical College, Ghaziabad, Uttar Pradesh, India; 2Rehabilitation Research Chair, College of Applied Medical Sciences, King Saud University, Riyadh, Saudi ArabiaCorrespondence: Amir IqbalG95-1, Rehabilitation Research Chair, College of Applied Medical Sciences, King Saud University, P.O. Box.10219, Riyadh 11433, Saudi ArabiaTel +966 1 4696010Fax +9661 4693589Email ajamaluddin@ksu.edu.saPurpose: Balance is controlled through a complex process involving sensory, visual, vestibular and cerebral functioning which get affected by various neurological disorders such as in stroke. Various types of exercises are designed to address the imbalance that is developed due to these neurological disorders. This study aimed to compare the efficacy of dual-task training using two different priority instructional sets in improving gait parameters in patients with chronic stroke.Methods: This study was a randomized, pretest-posttest experimental group design that compared between two different priority instructional sets (fixed versus variable) of the dual-task training. A convenience sample of thirty patients with chronic stroke due to ruptured middle cerebral artery (mean age±SD = 55.76±5.23; range 48–65 years) was recruited and equally allocated into two groups. Group 1 received dual-task training with fixed priority instructional sets and group 2 received dual-task training with variable priority instructional sets. Both groups were trained for a period of 45 mins each session, 3-sessions per week for 4 weeks. The timed 10-m walk test and foot prints on walkway paper were used to assess the gait parameters (walking speed, stride length and step length) before and after the training session.Results: Within-group analysis revealed a significant improvement (p<0.05) on gait parameters for both the groups. Furthermore, Cohen’s d calculation for the treatment effect size revealed highly larger effect size on gait parameters in group 2 (Cohen’s d>2 SD) than group 1 (Cohen’s d<2 SD) for the all variables.Conclusion: The dual-task training with variable priority instructional sets (group 2) was more effective than dual-task training with fixed priority instructional sets (group 1) in improving gait parameters such as gait speed, stride length, and step length in patients with chronic stroke. Physiotherapists should spread awareness and use this specific set of exercises (variable priority instructional sets) while performing a dual-task balance training program among patients with chronic stroke.Keywords: stroke, gait velocity, stride length, step length, dual-task balance training, fixed priority training, variable priority training